The European Normative Response to the Data Society: From the GDPR to the AI Act (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This study aims to improve our understanding of how effective the European Union’s normative framework is at achieving its declared objective of shaping a digital society in which the adoption of AI systems does not endanger widespread respect for fundamental rights and democratic values. After providing an overview of the main features of the EU’s legal framework on AI, the study will conclude with recommendations on how to better shape a rights-oriented society that capitalizes on AI without compromising the EU’s values. The study will also propose the broader application of the precautionary principle to inform the innovation process, not just as an interpretative tool.
Keywords: artificial intelligence; fundamental rights; fundamental rights impact assessment - FRIA; precautionary principle